Cardiac biomarkers alterations in rapid weight loss and high-intensity training in judo athletes: a crossover pilot study - Milovancev, A.; Ilic, A.; Miljkovic, T.; Petrovic, M.; Stojšic Milosavljevic, A.; Roklicer, R.; Trivic, T.; Manojlovic, M.; Rossi, C.; Bianco, A.; Drid, P. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND Studies evaluating alterations in cardiac biomarkers in rapid sport-associated weight loss (RWL) and high-intensity sport-specific training (HISST) are lacking. This pilot study aimed to examine the effects of RWL and HISST on heart rate, blood pressure, cardiac biomarkers, and left ventricular systolic function. Nine elite male judokas participated in the presented survey.